Recombinant bromelain purification, powder formulations and its applications - Zatul Iffah binti Mohd Arshad (Kulliyyah of Engineering, International islamic University Malaysia, 2016)
Recombinant bromelain is a proteinase that was successfully expressed in Escherichia coli BL21-A1 host. Interestingly, recombinant bromelain has a potential for medicinal purposes to treat inflammatory-related diseases such as cancer as well as for meat tenderizer in food application. Rising demands of bromelain have encouraged the production of recombinant bromelain in high amount and purity. However, there is very limited scientific evidence on the purification, drying, and the application of this enzyme in food and as an anti-cancer agent. In this study, the purification efficiency of recombinant E.coli BL21-A1 was compared with different purification techniques including ammonium sulphate precipitation, affinity chromatography, ion exchange chromatography, gel filtration chromatography, and aqueous two-phase system (ATPS). The ATPS process comprising of 18.47 % (w/w) PEG6000 (polyethylene glycol 6000) and 13% (w/w) potassium phosphate at pH 7.0 proved to be more efficient, cost-effective (USD 426.08/system), time-saving (30 min), high purity (1.10±0.07) and high recovery (2.81±0.03 %). It is clear that ATPS technique raises the potential substitution of the ammonium sulphate precipitation chromatography process. Recombinant bromelain was formulated as spray-dried and freeze-dried in the solid-state to provide stabilization during storage, handling, and transportation. The formulation that consists of 20 % (w/w) maltodextrin and low concentration of PEG recombinant bromelain (10 % w/w) was applied to spray drying process under optimise conditions (inlet temperature of 120 °C, air flow rate of 666.93 l/hour, pump rate of 15 %, and aspirator rate of 100 %), resulting the specific activity of 3.21±0.02 unit/mg, yield of 9.77±0.58 %, moisture content of 4.75±0.16 % and outlet temperature of 72 °C. The spray-dried and freeze-dried recombinant bromelain offered high GDU (gelatin digestion unit) activity and display the ability to tenderize meat comparable to the commercial bromelain. The freeze-dried recombinant bromelain showed a higher cytotoxic effect (IC70 at 125.53 µg/ml) than the spray-dried formulation with no inhibitory activities as discovered by MTT (3-(4, 5-dimethylthiazol-2-yl)-2, 5-diphenyl tetrazolium bromide) assay. The reduction of tumor weight with the dose of 500 mg/kg with 1.687 units of an enzyme of freeze-dried recombinant bromelain by oral gavage route was observed through in vivo assay. The clonogenic study showed that treatment with freeze-dried recombinant bromelain reduced the number of metastatic tumour colonies for both cultures of lungs and livers from mice samples. A positive effect of IL-2 and IFN- and a negative effect of IL-1β and IL-10 for treated groups (freeze-dried recombinant bromelain), indicates the increased level of immunity and decrease the level of tumourigenesis. In conclusion, freeze-dried recombinant bromelain possessed anti-cancer properties against breast cancer cells in vitro and in vivo. As such, further studies are warranted to fully exploit the freeze-dried recombinant bromelain and spray-dried recombinant bromelain in food and pharmaceutical applications.